Local Characterization of Ultrathin ZnO Layers on Ag(111) by Scanning Tunneling Microscopy and Atomic Force Microscopy - Shiotari, Akitoshi; Liu, Bo-Hong; Jaekel, Simon; Grill, Leonhard; Shaikhutdinov, Shamil; Freund, Hans-Joachim; Wolf, Martin; Kumagai, Takashi (Journal of Physical Chemistry C, 2014)
We have studied the local structure of ultrathin ZnO layers grown on Ag(111) by the reactive deposition method using low-temperature scanning tunneling microscopy (STM) and noncontact atomic force microscopy (nc-AFM) at 5 K. The characteristic Moire patterns arising from the lattice mismatch between the ZnO(0001) layers and Ag(111) appear in STM, but it is not pronounced in nc-AFM images. This indicates an atomically flat geometrical structure of the ZnO layer and a dominant contribution of the electronic state to the Moire patterns imaged by STM. We found that the apparent height of STM for the ZnO layers strongly depends on the bias voltage and becomes comparable with that of nc-AFM when the bias voltage is below the conduction band edge of the ZnO layers. The ZnO layers with the STM (AFM) apparent height of 3.8 (4.0) +/- 0.3 and 5.8 (6.1) +/- 0.3 angstrom were observed. On the other hand, mapping the onset of the resonance state of the ZnO layer by scanning tunneling spectroscopy provides a basis for determining its thickness. Our results suggest that the ZnO layers on Ag(111) grow predominantly as bi- and trilayers under the conditions used.